Analysis of RF performance of novel Sc-doped GaN high-electron-mobility transistors with air-bridge structure - Peng-lin Wang (Elsevier, 2021)
We analysis the RF performance of novel Sc-Doped GaN high-electron-mobility transistors (HEMTs) with asymmetric air-bridge structure by TCAD software. The maximum oscillating frequency (fMAX) which has been achieved in this work is 41.2 GHz and the cutoff frequency (fT) reached 30.2 GHz, while the HEMT with conventional structure attained to only 12.9 GHz and 9 GHz respectively. This work has been performed on novel p-GaN HEMT device. The air-bridge is designed to be asymmetrical in width and the ScAlN layer is innovatively placed between the AlGaN and GaN layers as part of the heterojunction. It is found that the thickness change of scandium layer will bring great influence on a higher transconductance (from 9.22 × 10−3 S/mm to 3.187 × 10−2 S/mm), lower electron concentration (from 5.01 × 1019/cm3 to 3.16 × 1018/cm3) and higher electron velocity (from 5.52 × 107cm/s to 2.30 × 108cm/s) of the device. In addition, the combined influence of air bridge and scandium layer structure on the capacitance and other parameters were analyzed, which propose a useful approach for improving the DC and RF characteristic of GaN HEMTs.